2012
DOI: 10.1177/1049909111432625
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Use at the End of Life Among Hospitalized Patients With Advanced Cancer

Abstract: Antimicrobial use was common among patients with advanced cancer. Even after transition to comfort care, more than one third of patients remained on antimicrobials. The risks and burdens of antimicrobials should be carefully examined when comfort is the stated goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
77
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 22 publications
(38 reference statements)
3
77
1
3
Order By: Relevance
“…19,20 Other studies including patients with malignancies at the end of their life have found high rates of antibiotic use. 21 Data is limited and conflicting as to whether such treatments result in improved level of comfort. 22,23 Recently, POLST was found to lack impact on antibiotic administration in nursing home residents.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Other studies including patients with malignancies at the end of their life have found high rates of antibiotic use. 21 Data is limited and conflicting as to whether such treatments result in improved level of comfort. 22,23 Recently, POLST was found to lack impact on antibiotic administration in nursing home residents.…”
Section: Discussionmentioning
confidence: 99%
“…As we discussed in that article (5), there may be less incentive for diagnostic coding beyond the primary diagnosis in hospice care because therapy is directed at symptoms, and reimbursement is fixed at a per diem rate. Furthermore, in a study of hospitalized patients with advanced cancer who ultimately died in the hospital, only approximately 70% of patients who received antimicrobial therapy met clinical criteria for an infection (12).…”
Section: Discussionmentioning
confidence: 99%
“…Infections are common at the end of life. Nearly half of patients with advanced dementia, 90% of hospitalised patients with end‐stage cancer and over a quarter of patients in hospices are commenced on antimicrobials in the final 2 weeks of life . Despite the documented goal of care being to optimise symptom palliation and reduce burdensome interventions or treatments, antimicrobials are continued into the terminal phase (last few days of life) in more than one‐third of cancer patients …”
Section: Introductionmentioning
confidence: 99%
“…Nearly half of patients with advanced dementia, 90% of hospitalised patients with end-stage cancer and over a quarter of patients in hospices are commenced on antimicrobials in the final 2 weeks of life. [12][13][14] Despite the documented goal of care being to optimise symptom palliation and reduce burdensome interventions or treatments, antimicrobials are continued into the terminal phase (last few days of life) in more than one-third of cancer patients. 12 As almost three-quarters of Australian COPD patients die in hospital, 15 we hypothesised that these patients may receive more antimicrobials in a bid to preserve life, compared with those patients who survive exacerbations.…”
Section: Introductionmentioning
confidence: 99%